PENERAPAN ARSITEKTUR REGIONALISME RUMAH ADAT SAMOSIR PADA DESAIN PUSAT INFORMASI WISATA - Reformanda Fransiskus Simbolon; Endah Tisnawati (Tesa Arsitektur, 2026)
This study examines the transformation of regionalism architecture of Samosir traditional houses in the design of Tourist Information Centers (TIC) in the Lake Toba area. The research is motivated by the need for sustainable tourism development and the preservation of local cultural identity in Indonesia’s national priority destinations. The objective is to formulate design principles for TIC that integrate traditional architectural elements, such as roof form, local materials, spatial layout, and ornamentation, with modern demands for functionality, innovation, and sustainability. The study employs a qualitative-descriptive approach through literature review, visual analysis, and design exploration based on local context. Findings reveal that applying regionalism principles, via adaptation of roof forms, spatial zoning based on the Tri Tunggal Banua philosophy, and the use of Batak Toba ornaments and color schemes, strengthens local identity, enhances tourism appeal, and creates educational and inclusive public spaces. This research highlights the significance of regionalism architecture as a strategic approach for developing sustainable and culturally-based public tourism facilities.